Inflammasomes in Human Immunodeficiency Virus Type 1 Infection - Qiankun Wang; Liang Shan (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Innate immune responses are the host's first line of defense against human immunodeficiency virus type 1 (HIV-1) infection, with pattern recognition receptors detecting viral specific pathogen-associated molecular patterns and initiating antiviral responses. In response to HIV-1 nucleic acids or proteins, some pattern recognition receptors have the ability to assemble a large multiprotein complex called the inflammasome, which triggers pro-inflammatory cytokine release and a form of lytic programmed cell death called pyroptosis. Here, we review our current understanding of the mechanism of the inflammasome in sensing HIV-1 infection. Furthermore, we discuss the contribution of inflammasome activation in HIV-1 pathogenesis as well as potential strategies of targeting inflammasome activation for the treatment of HIV-1 infection.